Penyuluhan Pencegahan Bahaya Listrik dan Petir pada Instalasi Listrik Rumah Tangga di Lembang Dewata Kecamatan Mappak Kabupaten Tana Toraja - Syahir Mahmud (Batara Wisnu : Indonesian Journal of Community Services, 2022)
Tana Toraja Regency as one of the national tourist destinations within the administrative area of South Sulawesi Province. Tana Toraja Regency, which has a city in Makale, is located at 3°06'17"S South Latitude and 119°51'07" East Longitude. Tana Toraja Regency has an area of 2,054.30 km² and has a population of 270,489 people. Tana Toraja Regency consists of 19 sub-districts, one of which was chosen to be the location of community service for the Electrical Engineering Study Program, namely: Mappak Lembang Dewata District. The distance between the capital of Tana Toraja Regency and the provincial capital of South Sulawesi reaches 314 km. Electrical installations should be designed and installed on the basis of as required in the PUIL. In addition, the requirements for technical personnel who will install an electrical installation must be certified for competence in accordance with Law No.30 of 2009 concerning electricity. However, there are still often news of accidents caused by electric shocks, both those who died and those who were only limited to electric shocks. Such is the case with the danger of lightning that constantly lurks in other living things. This lightning has the potential to cause lifelong disability until death. For this reason, we from the Abmas Team of the Electrical Engineering Study Program, Faculty of Engineering, UAJ Makassar, are here to bridge between ordinary people about the potential dangers of electricity and lightning strikes and preventive efforts that can be done so that they can be avoided from the possibility of avoiding these accidents. The abmas team from the UAJM Electrical Engineering Study Program will help the community to explain how to overcome this which has become an obligation to carry out the duties of the Tri Darma of Higher Education, one of which is Community Service. The real form of community service that will be carried out is to provide counseling to the lembang dewata community about; How should efforts be made to avoid and prevent the occurrence of electrical accidents and lightning strikes that will be conveyed to the general public. This counseling explains the sources of electric shock hazards in a household installation and how to prevent them, along with the potential dangers of lightning strikes and how to avoid them. The material is delivered in the form of visualization of imaginative and communicative models and drawings